Maria de Lourdes Pintasilgo ou ops caminhos de cuidar o futuro - Joaquim, Teresa (Investigaciones Feministas (Feminist Research), 2010)
In this paper, I propose an examination of Maria de Lourdes Pintasilgo (1930- 2004), the first woman to be prime minister of Portugal, as well as the first woman candidate for the presidency. This proposal has to do with the reflection she elaborated in various international forums (UNESCO, OCDE, the European Parliament) on the meaning of care, and, with it, the meaning of caring for the future.
Keywords: Care; Feminism